Grice's Maxims: Investigate the Intent of the Infringements in “The Prince And The Pauper” Conversational Discourse - Maya Yolanda (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
Grice coins 4 maxims to govern daily conversation as a general rule. The maxims are Quantity, Performance, Value and Manner. On this basis, the author intends to address the breaches of Grice's maxims in film and to investigate the intent of the infringements in the Prince and the Pauper conversational discourse. Many sections of the film contain violations of Grice's maxim characters. The writer formulates two work problems in order to achieve these goals: Which of Grice's maxims was violated in The Prince and the Pauper movie by the addressees?; For what reasons are the maxims infringed by the addresses?. . Based on the analysis, the author argues that the characters, in particular Duke, Tom Canty, King, and the Earl of Hertford, have violated Grice's four maxims in the film dialogue. If they fail to provide sufficient information, tell their addressees to lie, provide irrelevant glosses, and fail to be real, concise, univocal, and orderly, they violate the Quantity, Value, Relevance, and Manner maxims, respectively. In reality, the writer believes that characters are breaching the maxims to trick colleagues, to be sweet, to save face, to avoid discussion, and to show self-interest.